Morphological changes of mucous membrane of maxillary sinus at odontogenic perforative sinusitis - O. D. Baydik; S. V. Logvinov; S. G. Zubarev; P. G. Sysolyatin; A. A. Gurin (Бюллетень сибирской медицины)
Methods of light, electronic microscopy and immunohystochemistry lead research of structural changes of a mucous membrane maxillary sinus at 43 patients with odontogenic perforative sinusitis. The material is broken into 4 groups depending on a limitation period of punching. Degenerate changes ciliated epithelial cells came to light already on early terms after perforations of sinusitis and were shown by reduction of specific volume of mitochondrias, the GER, increase NCR. In globlet exocrine cells reduction NCR is connected to infringement of evacuation of a secret. In terms more than 3 months occured metaplasia of epithelium in single-row cubic and multilayered flat with keratosis, increased cellular infiltration own plate of a mucous membrane maxillary sinus. The contents of CD4 + cells in a mucous membrane of sine gradually increased, and on late terms of occurrence of perforations decreased. The contents of CD8+ and СD20+ cells in a mucous membrane with perforations of sinusitis were raised.